2021
DOI: 10.13075/ijomeh.1896.01746
|View full text |Cite
|
Sign up to set email alerts
|

The level of knowledge of diabetic prevention in Poland – is there a phenomenon of pluralistic ignorance?

Abstract: Objectives:The main aim of this work is to assess the level of knowledge about diabetes prevention and the consequences of untreated diabetes in the Polish society, as well as to indicate the variables that have a significant impact on that knowledge. Material and Methods: The analysis is based on the results of the National Multicenter Health Survey -WOBASZ II. The number of subjects surveyed was 6170, including 2760 men and 3410 women, aged 20-74 years. Data on socio-demographic variables, lifestyle and subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In the WOBASZ study, more than three-quarters of participants were characterized by unsatisfactory level of knowledge about diabetes prevention, or about the consequences of untreated diabetes. 39 …”
Section: Discussionmentioning
confidence: 99%
“…In the WOBASZ study, more than three-quarters of participants were characterized by unsatisfactory level of knowledge about diabetes prevention, or about the consequences of untreated diabetes. 39 …”
Section: Discussionmentioning
confidence: 99%
“…AHTATS is a government unit dealing with health technology assessment (HTA), including issuing opinions on HPPs [24,25]. All LGUs are obliged to obtain the Agency's opinion on the drafts of their HPP before proceeding unless AHTATS has issued a general recommendation on a given health problem (ready-made program templates, which allow LGUs to National HPPs on diabetes prevention and control were analyzed in a number of papers [19,20,27,28]…”
Section: Introductionmentioning
confidence: 99%
“…Basing on many reliable studies, ESC recommends maintaining a normal weight, choosing a more plant-based and fiber-rich food pattern, replacing saturated fats with unsaturated, and avoiding highly processed foods that contain trans fats, simple sugar, salt and nitrates [6]. Unfortunately, the level of nutritional education in Poland is still too low [7][8][9][10][11]. The largest study assessing the diet and adherence to dietary recommendations on a representative group of Poles, conducted in 2013-14, showed that a significant percentage of Poles had inappropriate eating habits [12].…”
Section: Introductionmentioning
confidence: 99%